162 An Examination of Scar Modelling and Assessment Methods for the Evaluation of Scar Treatments. (4th May 2021) - Mistry, R
Abstract: Introduction: Scarring is the final common pathway for healing within the skin. Scars can be itchy, painful, tight, and disfiguring. Despite advances in surgery there is currently no reliably effective treatment for reducing or preventing scarring. The primary aim of this research is to assess the currently available models for scarring and evaluate/further develop the utility of current assessment tools, in an effort to design a pilot randomised control trial (RCT) for silicone gel treatment of scars. Method: A systematic review of scar models in humans and animals. Examination of currently used subjective and objective scar assessment tools in a plastic surgery scar clinic. A retrospective cohort study assessing long-term scar outcomes in paediatric burn patients. Results: Limitations and drawbacks of many existing methods to assess scar treatments were found. No statistically significant difference in long-term scarring outcomes was found between paediatric burns patients treated surgically versus conservatively. A RCT for silicone gel sheeting in the treatment of scars was set up and successful in recruitment. Conclusions: Here, we have demonstrated difficulties in establishing a scientific scar treatment model; and created a pilot study that will help to provide high-quality evidence for the efficacy of silicone gel sheeting as a treatment for scars.